The Effect Of Price Communication On Customer Satisfaction At Cangehgar Gym In Cirebon - Nafa Meliayana; Siti Khumayah; Aghnia Dian Lestari (Indonesian Journal Publisher, 2026)
The rapid growth of the fitness industry in Cirebon has led to increasingly fierce competition among fitness centers, making price communication one of the key factors in determining customer satisfaction levels at Cangehgar Gym Cirebon. This study was conducted to analyze the influence of price communication on customer satisfaction levels at Cangehgar Gym Cirebon using the Service Quality (SERVQUAL) approach, which encompasses the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. This study employs a quantitative method, specifically a survey using a Likert-scale questionnaire distributed to Cangehgar Gym Cirebon customers, with the sample size determined based on the Slovin formula. Data analysis was conducted through instrument validity testing, reliability testing, classical assumption testing, simple regression analysis, and hypothesis testing using SPSS 29 software. The resulting regression equation is Y = 4.560 + 0.569X + e, indicating that price has a positive impact on customer satisfaction. The coefficient of determination (R²) value of 0.715 indicates that 71.5% of customer satisfaction is influenced by the price factor. The results of this study show that aligning price communication with the quality of service and facilities provided can increase customer satisfaction at Cangehgar Gym Cirebon and serves as an important component of an effective marketing communication strategy.